Pengaruh Uang Saku, Gaya Hidup Dan Self Control Terhadap Minat Investasi Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Slamet Riyadi Surakarta - Rahma Ghisella Afiania; Edi Wibowo; Setyaningsih Setyaningsih (CV. ITTC INDONESIA, 2025)
This research uses a survey method conducted on students of the economics and business faculty at Slamet Riyadi University, Surakarta. The data required is a general description of the research object, respondents' responses regarding pocket money, lifestyle, self-control and student investment interest. The type of data used in this research is quantitative data. Data sources include primary and secondary data. Data collection techniques in research use questionnaires distributed to respondents. The sampling technique uses random sampling. The sample size in this study used the Slovin formula, 130 students from the economics faculty at Slamet Riyadi University, Surakarta. Data analysis techniques use descriptive analysis and inductive analysis in the form of multiple linear regression analysis, t test, F test (model accuracy), and coefficient of determination test (R²) The results of the t test show that pocket money has a significant effect on investment interest because it has a significance value of 0.008 < 0.05, lifestyle has a significant effect on investment interest because it has a significance value of 0.002 < 0.05, self control has a significant effect on investment interest because it has a significance value of 0.012 < 0.05. The F test results show that this regression has a calculated F value of 20.273 with a significance value of 0.000 < 0.05, meaning that the model is correct in predicting the influence of pocket money, lifestyle, self-control on investment interest. The coefficient of determination result is 0.309, which means that the influence given by the independent variables, namely pocket money, lifestyle, self-control, is 30.9%, while the remainder (100% - 30.9%) = 69.1% is influenced by external factors. variables studied